Microbial Signatures in Fertile Soils Under Long-Term N Management - Villamil, María B.; Kim, Nakian; Riggins, Chance W.; Zabaloy, María C.; Allegrini, Marco; Rodríguez-Zas, Sandra L. (Frontiers in Soil Science, 2021)
Long-term reliance on inorganic N to maintain and increase crop yields in overly simplified cropping systems in the U.S. Midwest region has led to soil acidification, potentially damaging biological N2 fixation, and accelerating potential nitrification activities. Building on this published work, rRNA gene-based analysis via Illumina technology with QIIME 2.0 processing was used to characterize the changes in microbial communities associated with such responses. Amplicon sequence variants (ASVs) for each archaeal, bacterial, and fungal taxa were classified using the Ribosomal Database Project (RDP). Our goal was to identify bioindicators from microbes responsive to crop rotation and N fertilization rates following 34-35 years since the initiation of experiments. Research plots were established in 1981 with treatments of rotation (continuous corn [Zea mays L.] (CCC) and both the corn (Cs) and soybean [Glycine max L. Merr.] (Sc) phases of a corn-soybean rotation], and of N fertilization rates (0, 202, and 269 kg N/ha) arranged as a split-plot in a randomized complete block design with three replications. We identified a set of 3 archaea, and 6 fungal genera responding mainly to rotation; a set of 3 bacteria genera 3 linked to N rates, and a set of bacteria (22) and fungal (12) taxa responded to N fertilizer only within CCC . Indicators associated with the N cycle were identified from each taxon, with a dominance of denitrifier- over nitrifier- groups. A nitrifier archaeon Nitrososphaera, and Woesearchaeota AR15, an anaerobic denitrifier, were part of the signature for CCC environments, decreasing in abundance with rotated management. The opposite response was recorded for Plectosphaerella, a potential N2O producer. N fertilization in CCC or CS systems decreased abundances of bacteria genera Variovorax and Steroidobacter, whereas Gp22 and Nitrosospira only showed this response under CCC. In this latter system, N fertilization increased abundances of denitrifiers Gp1, Denitratisoma, Dokdonella, and Thermomonas, and the fungus Hypocrea, a known N2O producer. Identified signatures could help future monitoring and comparison across cropping systems as we move towards more sustainable management practices. This is needed primary information to understand the potential for managing the soil community to reduce nutrient losses to the environment.